(untitled) (Innovative professional education, 2025)
Digital learning platforms play an important role in the professional training of future skilled workers, providing flexibility, accessibility and personalisation of the educational process. The article discusses the algorithm for developing such a platform, including needs analysis, architecture design, implementation of basic functions, integration of adaptive technologies, testing, and validation. Particular attention is paid to the use of modern digital technologies, such as artificial intelligence, big data, and gamification, to improve learning efficiency. The proposed algorithm contributes to the creation of a high-quality digital learning environment that meets the requirements of the labour market and modern educational standards. The presented approaches can be used to further optimise professional learning processes in various industries.